Наукові основи електрохімічної технології покриттів тернарними сплавами заліза з тугоплавкими металами - Єрмоленко, Ірина Юріївна (НТУ "ХПІ", 2018)
Дисертація на здобуття наукового ступеня доктора технічних наук за спеціальністю 05.17.03 ‒ технічна електрохімія. ‒ Національний технічний університет "Харківський політехнічний інститут", Харків, 2018. Дисертацію присвячено розробці наукових основ електрохімічних технологій покриттів тернарними сплавами заліза та кобальту з молібденом і вольфрамом підвищеної функціональності. Експериментально доведено гіпотезу що-до конкурентного відновлення металів тріади заліза з тугоплавкими компонентами, обумовленого взаємним впливом термодинамічних, кристалохімічних характеристик сплавотвірних металів і кінетичних параметрів катодного процесу. Встановлено кінетичні закономірності співвідновлення в системах Fe³⁺ ‒ MoO₄²⁻ ‒ WO₄²⁻ ‒ Cit³⁻, Fe³⁺ ‒ Со²+ ‒ WO₄²⁻ (MoO₄²⁻) ‒ Cit³⁻ і обґрунтовано механізм осадження тернарних сплавів Fe-Mo-W, Fe-Co-W(Mo). Визначено вплив складу електролітів і режимів електролізу на елементний, фазовий склад і морфологію поверхні одержаних покриттів. Доведено можливість керування складом та морфологією багатокомпонентних покриттів на основі заліза і кобальту варіюванням складу електроліту (співвідношення концентрацій компонентів, співвідношення ліганду і комплексотвірників) і застосуванням гальваностатичного та імпульсного режимів електролізу з варіюванням густини струму 2,5 ‒ 6,5 А/дм², тривалості імпульсу / паузи 5 ‒ 10 / 5 ‒ 20 мс. Розроблено електроліти та режими осадження, що забезпечують осадження покриттів Fe-Co-W з вмістом Со 32 ‒ 47 ат. %, W 5 ‒ 13 ат. %, покриттів Fe-Mo-W з вмістом вольфраму 5 ‒ 11 ат. %, молібдену 26 ‒ 32 ат. % і покриттів Fe-Сo-Мо з діапазоном вмісту Сo 26 ‒ 48 ат. % і Мо 15 ‒ 31 ат. % та виходом за струмом до 58 – 82 %. Розроблено варіативні схеми електрохімічних процесів осадження покриттів сплавами Fe-Mo-W, Fe-Co-W(Mo) залежно від їх практичного застосування. За результатами експериментальних досліджень і тестувань функціональних властивостей покриттів в модельних середовищах і технологічних умовах визначено перспективні напрямки застосування одержаних матеріалів.

Dissertation for the Degree of the Doctor of Engineering Sciences in the Specialty of 05.17.03 – Technical Electrochemistry. – National Technical University "Kharkіv Polytechnic Institute", Kharkіv, 2018. This doctoral thesis is devoted to the development of scientific basics for electrochemical technologies used for the application of coatings consisting of ternary iron and cobalt alloys combined with molybdenum and tungsten of improved functionality. The hypothesis as for the competitive reduction of iron ternary metals with refractory components preconditioned by the mutual interaction of thermal-&-dynamic and crystal-&-chemical characteristics of the alloy-forming metals and the kinetic parameters of cathode process and it was proved experimentally. The kinetic regularities of the co-reduction in Fe³⁺ ‒ MoO₄²⁻ ‒ WO₄²⁻ ‒ Cit³⁻, Fe³⁺ ‒ Со²+ ‒ WO₄²⁻ (MoO₄²⁻) ‒ Cit³⁻ systems have been defined and the mechanism of deposition of ternary Fe-Mo-W, Fe-Co-W (Mo) alloys has been substantiated. The influence of composition of electrolytes and modes of electrolysis on elemental, phase composition and surface morphology of the obtained coatings has been deter-mined. The possibility of controlling the composition and morphology of multicomponent coatings on the basis of iron and cobalt by varying the composition of the electrolyte (the ratio of component concentrations, the ratio of ligand and complexing agent), and by used of galvanostatic and pulsed electrolysis regimes with a ranging of current density 2.5 ‒ 6.5 A/dm², and durations pulse/pause 5 ‒ 10 / 5 ‒ 20 ms, has been proved. The electrolytes and the deposition modes were developed that provide the deposition of Fe-Co-W coatings with the Co content of 32 to 47 аt. %, and W of 5 to 13 аt. %, and Fe-Mo-W coatings with the tungsten content of 5 to 11 at. %, and the molybdenum contents of 26 to 32 at. %, and the Fe-Сo-Мо coatings with the Co content ranging from 26 to 48 at. %, and Mo content ranging from 15 to 31 at. %, and the current efficiency ranging from 58 to 82 %. The variation schemes of electrochemical processes were suggested and these allow for the deposition of Fe-Mo-W and Fe-Co-W(Мо) coatings depending on their practical application. The perspective directions of the application of the obtained materials according to the results of experimental researches and tests of functional properties in model environments and technological conditions are determined.
Scientific Basics of Electrochemical Technology For Applying Coatings Consisting of Ternary Iron Alloys with Refractory Metals
Keywords: вольфрам; електрохімічне осадження; залізо; імпульсний електроліз; каталітична активність; кобальт; магнітні матеріали; молібден; тернарні сплави; дисертації; tungsten; electrochemical deposition; iron; pulse electrolysis; catalytic activity; cobalt; magnetic materials; molybdenum; ternary alloys; 621.35